Identification of gut contents and microscopical observations of the gut epithelium of the macrophagous ascidian Cibacapsa gulosa Monniot and Monniot 1983 (Phlebobranchia, Octacnemidae) - Lescano, M.N.; Fuentes, Veronica; Sahade, Ricardo; Tatián, Marcos (Polar Biology, 2011)
8 pages, 5 figures, 2 tables Octacnemids represent a different pathway in the evolution of the typical filter-feeding ascidians. We examine and identify the prey items in the gut contents and describe the cell types that constitute the inner wall of different sections of the gut of the macrophagous octacnemid Cibacapsa gulosa collected in the South Sandwich Islands, Antarctica. A great variety of prey items were found: polychaetes, copepods, halacarids, amphipods, isopods and ophiuroids. The internal wall of the gut is lined with a monostratified, prismatic epithelium. Different cell types occur in the inner wall in different sections. The presence of zymogenic cells throughout the internal gut epithelium, as well as the presence of concretion cells in the stomach of C. gulosa, also present in the macrophagous tunicate group Sorberacea (= Hexacrobylidae), can be considered as an adaptation to the macrophagous diet This study was supported by the Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Instituto Antártico Argentino (IAA), Alfred Wegener Institute (AWI) and the Universidad Nacional de Córdoba (UNC). This work was partially funded by PICTO ANPCyT-DNA N8 36326 and SECyT (05/I602), Universidad Nacional de Córdoba Peer reviewed